2018
DOI: 10.5194/amt-11-6761-2018
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical properties derived from POLDER-3/PARASOL (2005–2013) over the western Mediterranean Sea – Part 1: Quality assessment with AERONET and in situ airborne observations

Abstract: The western Mediterranean atmosphere is impacted by a variety of aerosol sources, producing a complex and variable mixture of natural and anthropogenic particles, with different chemical and physical properties. Satellite sensors provide a useful global coverage of aerosol parameters but through indirect measurements that require careful validation. Here we present the results of a long-term regional scale analysis of the full dataset (March 2005 and October 2013) of POLDER-3/PARASOL ocean operational retrieva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 95 publications
0
30
0
Order By: Relevance
“…This calibration was done after the campaign but with similar tuning conditions. The sea salt SO 2− 4 (ss-SO 2− 4 ) was calculated as 0.252 • 0.3 • [seasalt], where 0.252 is the mass ratio of SO 2− 4 to Na + in sea salt and 0.3 is the mass ratio of Na + to sea salt (Ghahremaninezhad et al, 2016). Given these assumptions, the uncertainty in the sea salt concentrations is likely to be significantly higher than the typical 20 %, although the total contribution of sea salt to the PM 1 fraction was very small (0.30 µg m −3 ; <4 %).…”
Section: Analysis Of the Ctof-ams Datamentioning
confidence: 99%
“…This calibration was done after the campaign but with similar tuning conditions. The sea salt SO 2− 4 (ss-SO 2− 4 ) was calculated as 0.252 • 0.3 • [seasalt], where 0.252 is the mass ratio of SO 2− 4 to Na + in sea salt and 0.3 is the mass ratio of Na + to sea salt (Ghahremaninezhad et al, 2016). Given these assumptions, the uncertainty in the sea salt concentrations is likely to be significantly higher than the typical 20 %, although the total contribution of sea salt to the PM 1 fraction was very small (0.30 µg m −3 ; <4 %).…”
Section: Analysis Of the Ctof-ams Datamentioning
confidence: 99%
“…This algorithm, described in details by Herman et al (2005) and Tanré et al (2011), has been slightly improved in collection 3 regarding non-spherical particles in the coarse mode (Formenti et al, 2018). Briefly, it is based on the total and polarized radiances measured at 670 and 865 nm.…”
Section: Polder-3 Instrument and Derived Aerosol Operational Productsmentioning
confidence: 99%
“…CC BY 4.0 License. microphysical models (described in Table S1 in the Supplement of Formenti et al, 2018), the algorithm recalculates for each clear sky pixel the observed polarized radiances at several observational angles. Importantly, in the aerosol models used for the inversion, aerosols are considered as non-absorbing (the imagery part of the refractive index is assumed as zero) and the real part of their refractive index is invariant between 670 and 865 nm.…”
Section: Polder-3 Instrument and Derived Aerosol Operational Productsmentioning
confidence: 99%
See 2 more Smart Citations